Um novo jogo para o estudo do raciocínio combinatório e do cálculo de probabilidade - Lopes, José Marcos [UNESP]; De Carvalho Rezende, Josiane [UNESP] (My University, 2010)
We present an educational proposal for the study of combinatorial reasoning and calculation of probabilities based on a game and problem solving methodology, aiming to support the teaching of mathematical content. A review of the literature related to the teaching and learning of the concepts of combinatorial reasoning and probability is presented. The game is original, using a board game similar to Tic-tac-toe, and the movements of its parts have some similarities, in particular those made with the rook and pawn pieces of the game of chess. We formulate various activities (problems) involving the game which, in the process of solving them, using the problem solving methodology and with the appropriate intervention of the teacher, encourage students to develop strategies for counting, an indispensable tool in the initial study of Combinatorial Analysis and Calculation of Probabilities.
A new game for the study of combinatorial reasoning and calculation of probability
Keywords: Combinatorial reasoning; Games; Probability; Problem solving